2017
DOI: 10.1186/s12937-017-0280-3
|View full text |Cite
|
Sign up to set email alerts
|

Circulating magnesium levels and incidence of coronary heart diseases, hypertension, and type 2 diabetes mellitus: a meta-analysis of prospective cohort studies

Abstract: BackgroundData on the associations between circulating magnesium (Mg) levels and incidence of coronary heart diseases (CHD), hypertension, and type 2 diabetes mellitus (T2DM) are inconsistent and inconclusive. The aim of this study was to examine circulating Mg levels in relation to incidence of CHD, hypertension, and T2DM.MethodsProspective cohort studies published before May 2017 were searched through PubMed, EmBase, SCOPUS, and Google Scholar. A total of 11 studies that reported multivariable-adjusted assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 63 publications
0
51
1
5
Order By: Relevance
“…Due to the cross-sectional nature of our study, more factors determining the low plasma magnesium in type-2 diabetic subjects could not be investigated. However, some cohort studies have prospectively analyzed the incidence of new cases of type-2 diabetes and have reported an inverse association with plasma magnesium concentrations [51,[82][83][84], minimizing the cross-sectional bias. Thus, in a cohort of more than 12,000 nondiabetic subjects from the Atherosclerosis Risk in Communities Study during 6 years of follow-up [82], the authors detected an approximate two-fold statistically significant increase in incidence rate of type-2 diabetes comparing the highest to the lowest (categorized into 6 groups).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the cross-sectional nature of our study, more factors determining the low plasma magnesium in type-2 diabetic subjects could not be investigated. However, some cohort studies have prospectively analyzed the incidence of new cases of type-2 diabetes and have reported an inverse association with plasma magnesium concentrations [51,[82][83][84], minimizing the cross-sectional bias. Thus, in a cohort of more than 12,000 nondiabetic subjects from the Atherosclerosis Risk in Communities Study during 6 years of follow-up [82], the authors detected an approximate two-fold statistically significant increase in incidence rate of type-2 diabetes comparing the highest to the lowest (categorized into 6 groups).…”
Section: Discussionmentioning
confidence: 99%
“…[83] analyzed the risk conferred by hypomagnesemia of new onset type-2 diabetes after 10 years of follow-up and estimated a relative risk (RR) of 2.5; (95%CI: 1.1-4.1). In a meta-analysis of the published cohort studies [51], the pooled RR for incidence of type-2 diabetes comparing the highest to the lowest category of magnesium concentrations was RR: 0.64; 95% CI: 0.50-0.81). Likewise, numerous cohort studies analyzing dietary magnesium intake also found a protective effect, though of less magnitude.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Наряду со многими другими факторами в развитии, по крайней мере, некоторых вариантов АГ существенное значение могут иметь изменения гомеостаза двухвалентных катионов. При этом многие вопросы о роли кальция и магния в регуляции сосудистого тонуса и уровня артериального давления остаются спорными [1][2][3]. Особую актуальность роль двухвалентных катионов в развитии АГ приобретает в регионах, где питьевая вода имеет низкое содержание Ca 2+ и Mg 2+ (Северо-Запад России, в том числе и Санкт-Петербург, Скандинавские страны).…”
Section: Introductionunclassified
“…shown that there is a correlation between CHD and metabolic syndrome (MetS), T2DM, and elevated levels of inflammatory and oxidative stress biomarkers [2,3]. Several researches indicated that levels of magnesium and zinc considerably decreased in patients suffering from CHD and T2DM [4,5].…”
mentioning
confidence: 99%